2000
DOI: 10.1007/s002940000124
|View full text |Cite
|
Sign up to set email alerts
|

Recombination between divergent sequences leads to cell death in a mismatch-repair-independent manner

Abstract: Homologous recombination is an important DNA repair mechanism in vegetative cells. During the repair of double-strand breaks, genetic information is transferred between the interacting DNA sequences, thus creating a gene-conversion event. Gene conversion of a functional member of a gene family, which uses an inactive member (such as a pseudogene) as a template, might have deleterious consequences. It is therefore important for the cell to prevent recombination between divergent sequences. We have studied the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…It is important to note that consistent with our previous results (16), mitotic gene conversion with both LYS2 and ura3 sequences can take place in vegetative cells in the absence of a functional MMR system. This is different from what the current models for recombination predict and from what is observed in MMR Ϫ cells undergoing meiosis, in which gene conversion is greatly reduced (4,8,14,19,39).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is important to note that consistent with our previous results (16), mitotic gene conversion with both LYS2 and ura3 sequences can take place in vegetative cells in the absence of a functional MMR system. This is different from what the current models for recombination predict and from what is observed in MMR Ϫ cells undergoing meiosis, in which gene conversion is greatly reduced (4,8,14,19,39).…”
Section: Discussionsupporting
confidence: 91%
“…The second copy, located on another chromosome, carries a similar site containing a single-base-pair mutation that prevents recognition by the endonuclease (ura3-HOcs-inc) (43). In addition, the two ura3 alleles differ at two restriction sites, located to the right (BamHI) and to the left (EcoRI) of the HOcs-inc insertion; these polymorphisms are used to monitor the transfer of genetic information between the chromosomes (15,16). In these strains the HO gene is under the transcriptional control of the GAL1 promoter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple explanation for the coupling and directionality is that a short stretch of the invading DNA is degraded (e.g., by the editing functions of the DNA polymerase) before engaging in DNA synthesis. We favor this model because it has previously been shown that gene conversion in our system is not affected by mutations in the mismatch repair genes (15), whereas mutations in the editing domain of polymerase delta do affect gene conversion (Y. Aylon and M. Kupiec, unpublished data; see also reference 37).…”
Section: Resultsmentioning
confidence: 99%